SPEAKING PROBLEMS IN VOCATIONAL HIGH SCHOOL - Situmorang, Winda Meyana; Sirait, Sherina Romeini; Sipayung, Viki Suhariaty; Situmorang, Megawati; Napitupulu, Selviana (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
The purpose of this study is to discover the issues that frequently arise among students at one of the SMK Insani International Pematangsiantar. The students were found to have the following issues: For starters, the pupils had difficulty pronouncing some terms, particularly those with nearly identical pronunciations, such as leave (pergi) - life (tinggal), dessert (hidangan penutup) - Desert (gurun pasir), and snack (cemilan) - snake (ular). Besides that, apprehension about making mistakes and a lack of confidence when speaking English. This study was conducted using the Direct Method, which is a method of teaching foreign language subject matter in which the teacher directly uses a foreign language as the language of instruction, rather than using the students' native language, and where the teacher uses some tricks to pique the students' interest so that they do not become bored while learning English using this method. This research reveals that, pupils are no longer perplexed when pronouncing words that seem similar and are less fearful of making mistakes, implying that they are more secure in speaking English.